Behavioral Treatment for Speech and Language in Primary Progressive Aphasia and Primary Progressive Apraxia of Speech: A Systematic Review - Lisa D. Wauters; Karen Croot; Heather R. Dial; Joseph R. Duffy; Stephanie M. Grasso; Esther Kim; Kristin Schaffer Mendez; Kirrie J. Ballard; Heather M. Clark; Leeah Kohley; Laura L. Murray; Emily J. Rogalski; et al. (Neuropsychology Review, 2024)
Primary progressive aphasia (PPA) and primary progressive apraxia of speech (PPAOS) are neurodegenerative syndromes characterized by progressive decline in language or speech. There is a growing number of studies investigating speech-language interventions for PPA/PPAOS. An updated systematic evaluation of the treatment evidence is warranted to inform best clinical practice and guide future treatment research. We systematically reviewed the evidence for behavioral treatment for speech and language in this population. Reviewed articles were published in peer-reviewed journals through 31 May 2021. We evaluated level of evidence, reporting quality, and risk of bias using a modified version of the American Speech-Language Hearing Association (ASHA) Levels of Evidence, an appraisal point system, additional reporting quality and internal/external validity items, and, as appropriate, the Single Case Experimental Design Scale or the Physiotherapy Evidence Database – PsycBITE Rating Scale for Randomized and Non-Randomized Controlled Trials . Results were synthesized using quantitative summaries and narrative review. A total of 103 studies reported treatment outcomes for 626 individuals with PPA; no studies used the diagnostic label PPAOS. Most studies evaluated interventions for word retrieval. The highest-quality evidence was provided by 45 experimental and quasi-experimental studies (16 controlled group studies, 29 single-subject designs). All ( k = 45/45) reported improvement on a primary outcome measure; most reported generalization ( k = 34/43), maintenance ( k = 34/39), or social validity ( k = 17/19) of treatment for at least one participant. The available evidence supports speech-language intervention for persons with PPA; however, treatment for PPAOS awaits systematic investigation. Implications and limitations of the evidence and the review are discussed.